Research on Inheritance for Children from Sirri Marriage Based on the Compilation of Islamic Law - Nabilla Ayu Suraya; Akhmad Khisni; Munsharif Abdul Chalim (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Sirri marriage is a marriage that is carried out by a couple without notification (registered) at the Office of Religious Affairs (KUA), but this marriage has fulfilled the elements of marriage in Islam, which includes two brides, two witnesses, a guardian, consent, and also the dowry. This marriage Sirri is legal according to religion, but not according to positive law (state law). Inheritance right is a law that regulates that the inheritance of a person who has passed away is given to those who are entitled, such as families and communities who are more entitled. Meanwhile, the inheritance rights obtained by the child resulting from the Sirri marriage can only be obtained from the mother, unless the biological father recognizes and grants the inheritance right which is called wajibat. The research method used is the normative juridical approach, the specification of research by means of an approach that is carried out based on the main legal material by examining theories, concepts, legal principles and legislation related to this research, the data used are primary data and secondary which consists of primary legal materials and secondary legal materials, the data collection techniques used are through library research and field studies. Based on the results of the research, it can be concluded that first, the construction of inheritance rights for children resulting from Sirri marriages based on the Marriage Law, and KHI, children resulting from Sirri marriages only receive inheritance rights in the form of compulsory wills, according to Article 862 to Article 866 of the Civil Code states if the deceased leaves legal descendants, then outside wed children get 1/3 of the share that should be received if they are legitimate children (Article 863 of the Civil Code), inheritance only applies to children outside wedlock who are recognized by the father and/or mother if they are not recognized from father/mother, outside children do not have the right to inherit. Second, the legal consequence of Sirri marriage is that children born out of wedlock or illegitimate are not entitled to inherit from their father. Third, the judge's consideration in deciding the case Number 0177/Pdt.P/2014/PA.Jbg based on the Supreme Court decision Number 46/PUU-VIII/2012 article 43 paragraph 1, namely obtaining the right to demand education financing while according to article 1365 of the Civil Code, civil rights, lineage inheritance, guardian of marriage or any civil rights that are not included in Islamic law are not included in the relationship between father and son that occurs because of a Sirri marriage but can receive a mandatory will. Suggestions before deciding to marry Sirri please think about the many negative impacts behind a Sirri marriage.